SLAMF8 and NINJ2 promote neuroinflammation and oxidative stress through TLR4 NF kappa B pathway in Alzheimer’s disease - Shuo Liu; Yuze He; He Chen; Wenwen Zhao; Heman Xu; Tao Bai; Juan Feng (Scientific Reports)
Abstract This study aimed to investigate the expression and role of Signaling Lymphocytic Activation Molecule Family Member 8 (SLAMF8) in Alzheimer’s disease (AD), particularly its interaction with NINJ2 in the TLR4/NF-κB signaling pathway. SLAMF8 expression levels in AD models were analyzed using the Gene Expression Omnibus (GEO) database. Validation of SLAMF8 expression was conducted through RT-PCR and Western blot in Aβ1−42-exposed SH-SY5Y cells, LPS-exposed HMC3 cells, and APP/PS1 transgenic mice. The interaction between SLAMF8 and NINJ2 was explored through co-immunoprecipitation, confocal immunofluorescence, and Western blot analyses, focusing on their roles in the TLR4/NF-κB signaling pathway. SLAMF8 was significantly upregulated in AD models, and its overexpression activated the TLR4/NF-κB signaling pathway, leading to increased levels of pro-inflammatory cytokines and oxidative stress. NINJ2 was identified as a direct functional partner of SLAMF8, with co-localization observed in the cytoplasm. Knockout of NINJ2 abolished SLAMF8-mediated activation of the TLR4/NF-κB pathway, neuroinflammation, and oxidative stress. The SLAMF8-NINJ2-TLR4/NF-κB axis is a crucial signaling pathway in AD progression. SLAMF8 and NINJ2 emerge as potential therapeutic targets for managing AD, with significant implications for future research and clinical interventions.